Surface antioxidant for tinned circuit board and preparation method of surface antioxidant
By applying antioxidant mixed with crosslinked polyamic acid and inorganic nanoparticles on the surface of the circuit board after tin plating, the problem of oxidation of the circuit board after tin plating is solved, and higher high temperature resistance, humidity and heat resistance and mechanical properties are achieved, and the welding and electrical properties of the circuit board are significantly improved.
Patent Information
- Application Number
- CN202510368709.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The tin-plated circuit board is easily oxidized in the air, resulting in a decrease in welding performance and an impact on electrical performance. The existing sealing and packaging methods are costly and have limited protection effects.
A surface antioxidant after tin plating of circuit board is adopted to form polyamic acid by mixing dianhydride monomer, diamine monomer and solvent, and a crosslinking agent is added for crosslinking reaction. The antioxidant is formed by combining inorganic nanoparticles, which provides double protection against high temperature, humidity and heat, oxidation and mechanical properties.
The antioxidant showed higher stability than the traditional chromate passivation film in the 85°C/85%RH accelerated aging test, which significantly improved the welding performance and electrical performance of the circuit board and extended the service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of circuit board processing, and in particular relates to an antioxidant for the surface of a circuit board after tinning and a preparation method thereof. Background Art
[0002] In today's rapidly developing electronic information industry, circuit boards are the core components of various electronic devices, and their performance and quality are directly related to the stability and reliability of electronic devices. Tin plating is a commonly used surface treatment process in the circuit board manufacturing process. With the good conductivity, solderability and relatively low cost of tin, it can effectively enhance the electrical connection performance and welding effect of the circuit board, so it is widely used in circuit board surface treatment.
[0003] However, tinned circuit boards face serious oxidation problems in actual use. During production, storage, transportation and final use, circuit boards are inevitably exposed to the air. The oxygen in the air will react chemically with the tinned layer, causing the surface of the tin layer to gradually oxidize and generate oxides such as tin oxide. These oxides will not only change the appearance of the circuit board, causing it to lose its original metallic luster, but will also have a serious negative impact on the performance of the circuit board.
[0004] In terms of welding performance, the solderability of the oxidized tin layer is greatly reduced. When assembling circuit boards, good welding is the key to ensuring the stable electrical connection between electronic components and circuit boards. However, the oxide on the surface of the tin layer will hinder the effective combination of solder and the tin layer, causing problems such as cold soldering and desoldering, greatly increasing the failure rate of electronic products and reducing product quality and reliability. From the perspective of electrical performance, the oxide layer will increase the resistance of the circuit board and affect the current transmission efficiency, which will lead to unstable signal transmission of electronic equipment and affect the normal operation of the equipment.
[0005] To solve the above problems, traditional methods mainly use physical protection measures, such as sealed packaging. However, these methods have obvious limitations: on the one hand, sealed packaging can only delay oxidation to a certain extent and cannot fundamentally solve the problem; on the other hand, sealed packaging is expensive, and in actual applications, circuit boards need to be frequently opened and used, which greatly reduces the protective effect of sealed packaging.
[0006] For example, CN107447220A discloses a chromium-free environmentally friendly antioxidant and a preparation method. The chromium-free environmentally friendly antioxidant of the present invention uses azoles and their derivatives as the main raw materials, and azoles and their derivatives include the following substances: benzotriazole, methylbenzotriazole and 4-methylimidazole. The chromium-free environmentally friendly antioxidant of this application does not contain chromium and phosphorus, is environmentally friendly, has little pollution to the environment, is easy to clean and has no residue, but the corrosion inhibition effect of benzotriazole (BTA) is significantly reduced in an acidic environment with a low pH value, which may affect the application effect of the antioxidant in specific industrial scenarios (such as electroplating acidic solutions), and when free chlorine (such as hypochlorite) exists in the environment, the antioxidant effect of BTA will be destroyed and it will not be restored until the chlorine disappears.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The purpose of the present invention is to provide a circuit board surface antioxidant after tinning and a preparation method thereof. The antioxidant obtained by the present invention has excellent high temperature resistance, moisture and heat resistance, oxidation resistance and mechanical properties.
[0009] In order to achieve the above object, the present invention provides the following technical solutions: In a first aspect, an embodiment of the present invention provides a method for preparing an antioxidant on the surface of a circuit board after tinning, comprising the following steps: The dianhydride monomer, the diamine monomer and the solvent are mixed to react to generate polyamic acid, a crosslinking agent is added to perform a crosslinking reaction to form a crosslinked polyamic acid, and the crosslinked polyamic acid is uniformly mixed with inorganic nanoparticles to obtain an antioxidant.
[0010] The invention improves the salt spray resistance, oxidation resistance, moisture and heat resistance, high temperature resistance, mechanical properties and the like of the polyamic acid as an antioxidant by using a variety of monomers, and the synthesis steps are simple and can be used on a large scale.
[0011] Specifically, in the reaction system, the highly polar environment constructed with N,N-dimethylacetamide as solvent provides ideal homogeneous conditions for multi-component polycondensation reactions, in which the synergistic effect of fluorinated monomers and rigid / flexible dianhydrides dominates the structure-activity relationship of polymer molecular chains. Specifically, the fluorinated alkane chain of 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediamine forms an intramolecular shielding layer through the synergistic effect between strongly electronegative fluorine atoms, significantly reducing the permeability of water molecules and oxygen, while the hexafluoroisopropylidene structure of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride not only enhances the rigidity of the polymer main chain, but its unique steric hindrance effect can also inhibit the rotational motion of the molecular chain, thereby improving the thermal stability of the material. The rigid benzene ring structure of pyromellitic dianhydride strengthens the interaction between molecular chains through π-π stacking, while the ether bond of 4,4'-(oxydimethylene)diphthalic anhydride introduces a flexible spacer group, and achieves a balance between mechanical strength and processing performance by adjusting the mobility of the chain segments. During the polycondensation reaction, diamine and dianhydride gradually form amide bonds through nucleophilic addition-elimination reactions, and the dynamic proton transfer mechanism of the carboxylic acid group makes the molecular weight distribution of the linear polyamic acid chain tend to be uniform. When 1,3,5-tris(4-aminophenoxy)benzene is introduced as a crosslinker, its three amino active sites react with the carboxylic acid groups at the ends of the PAA chains. The process follows a step-by-step polymerization mechanism: first, the amino group nucleophilically attacks the carboxylic acid group generated by the ring opening of the anhydride to form an amide bond and release water molecules; then, the unreacted amino group continues to react with the carboxylic acid groups of the adjacent segments, and finally constructs a three-dimensional network structure. It is worth noting that the phenoxy structure of TAPOB can stabilize the reaction intermediates through the conjugation effect, and its planar rigid unit has a synergistic effect with the fluorinated groups in the main chain, further improving the material's resistance to moisture and heat. The final cross-linked polyamic acid solution exhibits a dual protection mechanism after film formation: on the one hand, the low surface energy layer formed by the fluorinated groups can repel water molecules and corrosive media; on the other hand, the steric hindrance effect generated by the cross-linked network effectively inhibits the diffusion of oxygen molecules to the metal interface, and its antioxidant performance shows higher stability than the traditional chromate passivation film in the 85℃ / 85%RH accelerated aging test.
[0012] From the perspective of molecular dynamics, the advantage of this material in the application of tin-plated anti-oxidation of circuit boards comes from its multi-level protection mechanism: at the microscopic level, the fluorinated group induces electron cloud deviation through the strong polarity of the CF bond, so that the metal surface forms a double electric layer to repel corrosive ions; at the mesoscopic level, the nanoscale pores in the cross-linked network can physically block the penetration of macromolecular corrosive media such as sulfides; and at the macroscopic level, the good matching of the thermal expansion coefficient of the material and the tin plating layer avoids interface peeling during temperature cycling. When applied to tin-plated circuit boards, the solution can self-assemble on the metal surface through an immersion process to form a dense protective film with a thickness of 50-200nm. This film layer undergoes a partial thermal imidization transformation during the subsequent reflow process (peak temperature 260℃), generating a stable structure containing an imide ring, and its decomposition temperature is much higher than the processing temperature, thereby ensuring the durability of the protective performance.
[0013] In a preferred embodiment, the dianhydride monomer is 4,4'-(hexafluoroisopropylidene) diphthalic anhydride, pyromellitic dianhydride, or 4,4'-(oxydimethylene) diphthalic anhydride.
[0014] In a preferred embodiment, the diamine monomer is 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediamine.
[0015] In a preferred embodiment, the solvent is N,N-dimethylacetamide.
[0016] In a preferred embodiment, the mass ratio of the dianhydride monomer, the diamine monomer and the solvent is (1-5):1:(50-100).
[0017] In a preferred embodiment, the reaction conditions are: reaction temperature is 30-50°C, and reaction time is 10-18h.
[0018] In a preferred embodiment, the cross-linking agent is 1,3,5-tris(4-aminophenoxy)benzene.
[0019] In a preferred embodiment, the mass ratio of the crosslinking agent to the diamine monomer is (0.2-0.5):1.
[0020] In a preferred embodiment, the conditions of the cross-linking reaction are: the reaction time is 2-4 hours.
[0021] In a preferred embodiment, the inorganic nanoparticles include the following preparation steps: Graphene oxide, ethylenediamine and a solvent are mixed, the pH is adjusted to 8-10, the reaction is stirred, and the inorganic nanoparticles are obtained by centrifugal washing and drying.
[0022] The invention further synergistically improves the mechanical properties, corrosion resistance, salt spray resistance, moisture and heat resistance and other properties of the antioxidant by cross-linking polyamic acid and amino-oxide graphene.
[0023] Specifically, the three-dimensional network skeleton of cross-linked polyamic acid forms dense cross-linking points through the polycondensation of rigid aromatic dianhydrides (such as APBIA, PMDA) and fluorinated diamines (TFMB). The hexafluoroisopropylidene and oxydimethylene structures in the main chain provide hydrophobic barriers, reduce surface energy and inhibit the penetration of water molecules, while the sheet structure of amino-oxide graphene is embedded in the network through π-π stacking and hydrogen bonding. The amino groups on its edges form dynamic covalent bonds with the carboxylic acid groups at the ends of polyamic acid, further strengthening the interfacial bonding force. This dual cross-linking mechanism not only improves the mechanical strength, but also forms a maze effect in the polymer matrix through the two-dimensional nanosheets of graphene, forcing corrosive ions such as Cl⁻ and SO4²⁻ in salt spray to diffuse in a tortuous manner, greatly extending the penetration path. In a humid and hot environment, the low polarity surface of the fluorinated group and the hydrophobic six-membered ring of graphene synergistically enhance the hydrophobic properties, while the high thermal conductivity of amino-oxide graphene can quickly dissipate local hygrothermal stress and avoid thermal oxidation degradation. High temperature tolerance comes from the synergistic effect of the rigid biphenyl structure of polyamic acid and the sp² hybridized carbon skeleton of graphene, in which the graphene sheets inhibit the thermal motion of polymer segments, making the material have excellent mechanical properties at high temperatures. This synergistic system achieves progressive anti-corrosion protection from molecular-level interface strengthening to macroscopic performance improvement through multiple protection mechanisms of chemical bonding and physical isolation.
[0024] In a preferred embodiment, the particle size of the graphene oxide is 300-500 nm.
[0025] In a preferred embodiment, the mass ratio of graphene oxide, ethylenediamine and solvent is 1:(20-50):(100-200).
[0026] In a preferred embodiment, the solvent is a mixture of water and ethanol in a mass ratio of 1:1.
[0027] In a preferred embodiment, the stirring reaction conditions are: reaction temperature 50-80°C, reaction time 2-5h.
[0028] In a preferred embodiment, the mass ratio of the cross-linked polyamic acid to the inorganic nanoparticles is 100:(10-20).
[0029] In a second aspect, an embodiment of the present invention provides an antioxidant obtained by the above-mentioned method for preparing an antioxidant for the surface of a circuit board after tin plating.
[0030] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention improves the salt spray resistance, oxidation resistance, moisture and heat resistance, high temperature resistance, mechanical properties and other aspects of polyamic acid as an antioxidant through a variety of monomers, and the synthesis steps are simple and can be used on a large scale.
[0031] 2. The present invention further synergistically improves the mechanical properties, corrosion resistance, salt spray resistance, moisture and heat resistance and other properties of the antioxidant by cross-linking polyamic acid and amino graphene oxide. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Unless otherwise specified, all reagents used in the present invention are commercially available.
[0034] Graphene oxide, with an average particle size of 300 nm, was purchased from Nanjing Jicang Nanotechnology Co., Ltd.; 4'-(Hexafluoroisopropylidene)diphthalic anhydride was purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; Pyromellitic anhydride, purchased from Shanghai Oule Chemical Co., Ltd.; 4,4'-(oxydimethylene) diphthalic anhydride was purchased from Jiangsu Congzhong Chemical Co., Ltd.; 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediamine was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0035] Example 1 This embodiment provides a method for preparing an antioxidant on the surface of a circuit board after tinning, comprising the following steps: Synthesis of Inorganic Nanoparticles: By mass, 1 part of graphene oxide with an average particle size of 300 nm, 30 parts of ethylenediamine, 70 parts of water and 70 parts of ethanol were mixed, the pH was adjusted to 10, stirred and reacted at 65° C. for 3 h, and centrifuged, washed and dried to obtain inorganic nanoparticles.
[0036] Synthesis of antioxidants: By mass, 2 parts of 4'-(hexafluoroisopropylidene)diphthalic anhydride, 2 parts of pyromellitic dianhydride, 2 parts of 4,4'-(oxydimethylene)diphthalic anhydride, 2 parts of 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediamine and 70 parts of N,N-dimethylacetamide were mixed and reacted at 40°C for 12 hours to obtain polyamic acid, and then 0.3 parts of 1,3,5-tris(4-aminophenoxy)benzene was added for cross-linking for 3 hours to obtain cross-linked polyamic acid.
[0037] By weight, 10 parts of cross-linked polyamic acid and 1.2 parts of inorganic nanoparticles were mixed uniformly to obtain an antioxidant.
[0038] Example 2 This embodiment provides a method for preparing an antioxidant on the surface of a circuit board after tinning, comprising the following steps: Synthesis of Inorganic Nanoparticles: By mass, 1 part of graphene oxide with an average particle size of 300 nm, 40 parts of ethylenediamine, 80 parts of water and 80 parts of ethanol were mixed, the pH was adjusted to 10, stirred and reacted at 75° C. for 3 h, and centrifuged, washed and dried to obtain inorganic nanoparticles.
[0039] Synthesis of antioxidants: By mass, 3 parts of 4'-(hexafluoroisopropylidene)diphthalic anhydride, 3 parts of pyromellitic dianhydride, 3 parts of 4,4'-(oxydimethylene)diphthalic anhydride, 2 parts of 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediamine and 80 parts of N,N-dimethylacetamide were mixed and reacted at 40°C for 12 hours to obtain polyamic acid, and then 0.4 parts of 1,3,5-tris(4-aminophenoxy)benzene was added for cross-linking for 3 hours to obtain cross-linked polyamic acid.
[0040] By weight, 10 parts of cross-linked polyamic acid and 1.7 parts of inorganic nanoparticles were mixed uniformly to obtain an antioxidant.
[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that 2 parts of 4'-(hexafluoroisopropylidene)diphthalic anhydride, 2 parts of pyromellitic dianhydride, and 2 parts of 4,4'-(oxydimethylene)diphthalic anhydride are replaced by 3 parts of pyromellitic dianhydride and 3 parts of 4,4'-(oxydimethylene)diphthalic anhydride.
[0042] Comparative Example 2 The difference between this comparative example and Example 1 is that 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediamine is replaced by 2 parts of p-phenylenediamine.
[0043] Comparative Example 3 The difference between this comparative example and Example 1 is that 1.2 parts of inorganic nanoparticles are replaced with 0 parts of inorganic nanoparticles.
[0044] Comparative Example 4 The difference between this comparative example and Example 1 is that 1.2 parts of inorganic nanoparticles are replaced by 1.2 parts of graphene oxide having an average particle size of 300 nm.
[0045] Performance Testing The antioxidants obtained in the examples and comparative examples were coated on a substrate and kept in an oven at 200° C. for 2 h.
[0046] The salt spray resistance of the examples and comparative examples was tested according to GB / T 10125, and the results are shown in Table 1.
[0047] The antioxidants obtained from the examples and comparative examples were treated at 250° C. for 2 h, and then the salt spray resistance of the examples and comparative examples was tested according to GB / T 10125. The results are shown in Table 1.
[0048] The wet heat aging performance of the antioxidants of the examples and comparative examples was tested according to IPC-TM-650 2.6.14. The samples were placed in an environment of 85°C and 85% humidity for 168 hours. The failures were classified according to the severity of the failures, specifically: Class A: No visible migration or corrosion, insulation resistance remains stable.
[0049] Class B: Slight migration but no short circuit, insulation resistance decrease ≤ 10%.
[0050] Class C: Obvious migration or local short circuit, insulation resistance decrease > 10%.
[0051] Grade D: Severe short circuit or complete material failure.
[0052] The tensile strength of the antioxidants was obtained by testing the examples and comparative examples according to ASTM D638. The results are shown in Table 1.
[0053] The water contact angle was tested according to ASTM D7334. The results are shown in Table 1.
[0054] Table 1 Performance test results
[0055] It can be seen from the above performance test results that Examples 1-2 have the best high temperature resistance, moisture and heat resistance, oxidation resistance and mechanical properties, especially Example 2 has the most outstanding comprehensive performance, which is mainly due to the synergistic effect between the polyamic acid synthesized from multiple monomers of the present invention and the amino-treated graphene oxide.
[0056] The comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment in the corresponding performance test. This better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.
[0057] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an antioxidant for the surface of a circuit board after tinning, characterized in that: The following steps are involved: The dianhydride monomer, the diamine monomer and the solvent are mixed to react to generate polyamic acid, a crosslinking agent is added to perform a crosslinking reaction to form a crosslinked polyamic acid, and the crosslinked polyamic acid is uniformly mixed with inorganic nanoparticles to obtain an antioxidant.
2. The method for preparing an antioxidant for the surface of a circuit board after tinning according to claim 1, characterized in that: The dianhydride monomer is 4,4'-(hexafluoroisopropylidene) diphthalic anhydride, pyromellitic dianhydride, 4,4'-(oxydimethylene) diphthalic anhydride; and / or, the diamine monomer is 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediamine; And / or, the solvent is N,N-dimethylacetamide.
3. The method for preparing an antioxidant for the surface of a circuit board after tinning according to claim 1, characterized in that: The mass ratio of the dianhydride monomer, the diamine monomer and the solvent is (1-5):1:(50-100).
4. The method for preparing an antioxidant for the surface of a circuit board after tinning according to claim 1, characterized in that: The reaction conditions are: reaction temperature is 30-50°C, and reaction time is 10-18h.
5. The method for preparing an antioxidant for the surface of a circuit board after tinning according to claim 1, characterized in that: The cross-linking agent is 1,3,5-tris(4-aminophenoxy)benzene; And / or, the mass ratio of the cross-linking agent to the diamine monomer is (0.2-0.5):
1.
6. The method for preparing an antioxidant for the surface of a circuit board after tinning according to claim 1, characterized in that: The conditions of the cross-linking reaction are: the reaction time is 2-4h.
7. The method for preparing an antioxidant for the surface of a circuit board after tinning according to claim 1, characterized in that: The inorganic nanoparticles include the following preparation steps: Graphene oxide, ethylenediamine and a solvent are mixed, the pH is adjusted to 8-10, the reaction is stirred, and the inorganic nanoparticles are obtained by centrifugal washing and drying.
8. The method for preparing an antioxidant for the surface of a circuit board after tinning according to claim 7, characterized in that: The particle size of the graphene oxide is 300-500nm; And / or, the mass ratio of graphene oxide, ethylenediamine and solvent is 1:(20-50):(100-200); And / or, the solvent is a mixture of water and ethanol in a mass ratio of 1:1; And / or, the stirring reaction conditions are: reaction temperature 50-80° C., reaction time 2-5 h.
9. The method for preparing an antioxidant for the surface of a circuit board after tinning according to claim 1, characterized in that: The mass ratio of the cross-linked polyamic acid to the inorganic nanoparticles is 100:(10-20).
10. An antioxidant obtained by the method for preparing the antioxidant for the surface of a circuit board after tinning according to any one of claims 1 to 9.
Citation Information
Patent Citations
Chromium-free environment-friendly antioxidant and preparation method thereof
CN107447220A
Preparation method for low-dielectric-constant polyimide / multilayer graphene oxide composite film
CN104788676A
Transparent polyimide applied to flexible photoelectric field and preparation method thereof
CN113583443A
Flame-retardant flexible circuit board and preparation method thereof
CN119485936A
Polyimide precursor liquid composition and polyimide coating film
JP2004339363A